2018
DOI: 10.1016/j.plefa.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Bm -iAANAT and its potential role in fatty acid amide biosynthesis in Bombyx mori

Abstract: The purpose of this research is to unravel the substrate specificity and kinetic properties of an insect arylalkylamine N-acyltransferase from Bombyx mori (Bm-iAANAT) and to determine if this enzyme will catalyze the formation of long chain N-acylarylalkylamides in vitro. However, the determination of substrates and products for Bm-iAANAT in vitro is no guarantee that these same molecules are substrates and products for the enzyme in the organism. Therefore, RT-PCR was performed to detect the Bm-iAANAT transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…In applying this strategy to identify amine substrates for Bm -iAANAT3, a relatively high concentration of each amine (20 mM or 60 mM, Table 1) was included in the pool because the K m value for glycine is reported at ≥6 mM for some of the glycine N -acyltransferases [3840]. Pools of acyl-CoA substrates were not constructed because of the reports of long-chain acyl-CoAs acting as AANAT inhibitors [29,40,41]; therefore, we individually cross-screened amine pools against archetypal short and long-chain acyl-CoA thioesters, acetyl-CoA and oleoyl-CoA, because both have been reported as substrates for other GNAT family acyltransferases [20,21]. For Bm -iAANAT3, we found no initial velocity increase with oleoyl-CoA above the low enzyme-independent, background rate of oleoyl-CoA hydrolysis, suggesting that this enzyme does not catalyze the formation of long-chain N -acylamides.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In applying this strategy to identify amine substrates for Bm -iAANAT3, a relatively high concentration of each amine (20 mM or 60 mM, Table 1) was included in the pool because the K m value for glycine is reported at ≥6 mM for some of the glycine N -acyltransferases [3840]. Pools of acyl-CoA substrates were not constructed because of the reports of long-chain acyl-CoAs acting as AANAT inhibitors [29,40,41]; therefore, we individually cross-screened amine pools against archetypal short and long-chain acyl-CoA thioesters, acetyl-CoA and oleoyl-CoA, because both have been reported as substrates for other GNAT family acyltransferases [20,21]. For Bm -iAANAT3, we found no initial velocity increase with oleoyl-CoA above the low enzyme-independent, background rate of oleoyl-CoA hydrolysis, suggesting that this enzyme does not catalyze the formation of long-chain N -acylamides.…”
Section: Resultsmentioning
confidence: 99%
“…While fatty acid amides have been recently identified in B. mori [21], Bm -iAANAT3 is probably not involved in their biosynthesis in vivo . Bm -iAANAT3 accepts a variety of amines as substrates pointing towards a cellular role for this enzyme in amine inactivation and/or excretion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have proposed that novel iAANATs exist which will catalyze the acyl-CoA-dependent formation of these N -fatty acylamides (Figure 2 ). AANATs in D. melanogaster (Dempsey et al, 2014a ) and B. mori (Anderson et al, 2018 ; Battistini, 2015 ) have been identified that will utilize long-chain fatty acyl-CoA thioesters as substrates leading to the production of these fatty acylamides. Thus, we suggest replacing the name “ N -acetyltransferase” with “ N -acyltransferase” to better reflect the most current data on this family of enzymes.…”
Section: Introductionmentioning
confidence: 99%